Neovascular age-related macular degeneration without drusen in the fellow eye: clinical spectrum and therapeutic outcome - Chung WH; van Dijk EHC; Mohabati D; Dijkman G; Yzer S; de Jong EK; Fauser S; Schlingemann RO; Hoyng CB; Boon CJF (Clinical Ophthalmology, 2016)
Wing H Chung,1 Elon H C van Dijk,1 Danial Mohabati,1 Greet Dijkman,1 Suzanne Yzer,2 Eiko K de Jong,3 Sascha Fauser,4 Reinier O Schlingemann,5–7 Carel B Hoyng,3 Camiel J F Boon1,5 1Department of Ophthalmology, Leiden University Medical Center, Leiden, 2Rotterdam Eye Hospital, Rotterdam, 3Department of Ophthalmology, Donders Institute for Brain, Cognition and Behaviour, Radboud University Medical Center, Nijmegen, the Netherlands; 4Department of Ophthalmology, University Hospital of Cologne, Cologne, Germany; 5Department of Ophthalmology, 6Ocular Angiogenesis Group, Departments of Ophthalmology and Cell Biology and Histology, Academic Medical Center, 7Netherlands Institute for Neuroscience, Amsterdam, the Netherlands Purpose: To investigate the clinical characteristics and therapeutic outcome of patients with neovascular age-related macular degeneration (nAMD) in 1 eye, without drusen in the fellow eye. Patients and methods: Medical records of 381 patients were analyzed to identify the cases. The main outcomes included Early Treatment Diabetic Retinopathy Study (ETDRS) best-corrected visual acuity (BCVA) and change in central retinal thickness (CRT). These parameters were reviewed at baseline, first follow-up visit, and after 6, 12, and 24 months. Results: Out of 381 patients, 29 cases (8%) were included (of whom 3 had polypoidal choroidal vasculopathy [PCV]) who were treated with anti-vascular endothelial growth factor (anti-VEGF) therapy which was supplemented by photodynamic therapy (PDT) in the PCV patients. Overall, no statistically significant change in mean BCVA was observed during follow-up. BCVA improved or remained stable (defined as a gain in BCVA, a stable BCVA, or a loss of <5 ETDRS letters) in 22 patients (76%), and 7 patients (23%) had lost ≥5 ETDRS letters at final follow-up. A gain of ≥15 ETDRS letters at final follow-up was seen in 5 patients (17%). Mean CRT had decreased significantly with 99 µm (P<0.001) at 24 months after the initial visit. Conclusion: There is a clinical spectrum of nAMD that is not associated with drusen in the fellow eye. Patients with nAMD without drusen in the fellow eye respond to anti-VEGF treatment and, in cases of PCV, to supplemental PDT. The pathophysiology of this spectrum of nAMD may be different from drusen-associated age-related macular degeneration. Keywords: anti-vascular endothelial growth factor, unilateral age-related macular degeneration, non-neovascular age-related macular degeneration, polypoidal choroidal vasculopathy, precursor lesion, best-corrected visual acuity